2013
DOI: 10.1097/ico.0b013e318265682c
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic Alterations of the Palpebral Conjunctival Epithelium in a Dry Eye Model

Abstract: Purpose To investigate the normal palpebral conjunctival histology in C57BL/6 mice, and the structural changes that occur in a dry eye model. Methods 24 male and female C57BL/6 mice, 8 untreated (UT) and 16 exposed to experimental ocular surface desiccating stress (DS). Ocular dryness was induced by administration of scopolamine hydrobromide (0.5 mg/0.2 ml) QID for 5 (DS5) or 10 (DS10) days. Counts and measurements were obtained using anatomical reference points and goblet cell density was investigated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
4
16
0
Order By: Relevance
“…The same is true of the palpebral conjunctival epithelium in dry eyes in mice [5]. Extrapolation of the two findings seems to support the speculation of the thinning of the palpebral conjunctival epithelium in human dry eyes or in eyes wearing contact lens.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…The same is true of the palpebral conjunctival epithelium in dry eyes in mice [5]. Extrapolation of the two findings seems to support the speculation of the thinning of the palpebral conjunctival epithelium in human dry eyes or in eyes wearing contact lens.…”
Section: Discussionsupporting
confidence: 56%
“…An animal experiment has shown that the superior conjunctival epithelium is approximately 14 m thicker than the inferior [5]. Further studies are needed to ascertain if this is the case in the human and if the central region is different from the nasal or temporal region with respect to the palpebral conjunctival epithelium thickness.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Keratoconjunctivitis sicca (KCS), more commonly known as dry eye syndrome, is a multifactorial disease of the tear film and ocular surface that results in signs of discomfort, tear film instability, intense inflammation, and visual disturbance. [1][2][3][4] It may be quantitative, characterized by a deficiency in the production of the aqueous layer of the tear film, or qualitative, characterized by changes in the lipid layer of the tear film with rapid evaporation of tears. 3 KCS commonly affects dogs and is defined as a Schirmer tear test 1 (STT1) reading of less than 10 mm/ min concomitant with pathological changes in the ocular surface.…”
Section: Introductionmentioning
confidence: 99%
“…3,6,7 With regard to the pathophysiology of KCS, recent advances in the fields of cell biology and genetics suggest that it goes beyond the histopathological manifestations seen in the lacrimal gland and the ocular surface. 2,3,[8][9][10][11][12][13] There is evidence that the metabolism of cells on the surface of the palpebral conjunctiva is also severely altered by the disease. 2 In human patients, KCS has been closely associated with changes in interphase nuclear morphology of palpebral/bulbar conjunctival epithelial cells, and with the appearance of snake-like chromatin, whose clinical and biological significances remain under investigation.…”
Section: Introductionmentioning
confidence: 99%